Successful implementation of a clinical transition pathway for adolescents with juvenile-onset rheumatic and musculoskeletal diseases - Margot Walter; Sylvia Kamphuis; Philomine van Pelt; Annemarie de Vroed; Johanna M. W. Hazes (BMC, 2018)
Abstract Background In 2008 a clinical transition pathway for young people with juvenile-onset rheumatic and musculoskeletal diseases (jRMD) aiming at improving transitional care was instituted. Historical data on drop-out rate in our clinic was 35%, one year before the implementation of the transition pathway. This study aims to I) evaluate the effectiveness of the clinical transition pathway, II) evaluate the experiences and satisfaction of YP with the transitional process and evaluate their perceived self-management skills. Methods Young people with any jRMD transferred from the pediatric to the adult rheumatology department in our academic center were eligible to enroll in this quantitative cross-sectional observational study between 2009 and 2015. Notably in 2012, we created a dedicated adolescent JIA-clinic, located at the adult rheumatology department. Electronic patient records from all young people that were transferred between 2009 and 2015 were reviewed for drop-out of care. Young people were asked to rate a VAS for 'satisfaction with transition' and to complete the "on your own feet transfer experience scale" (OYOF-TES)-questionnaire regarding their experiences and satisfaction with transition. Self-management skills were measured with the "on your own feet self-efficacy scale" (OYOF-SES)-questionnaire. Results One hundred fifty-four young people were transferred to the adult department, of which 76 were transferred to the dedicated adolescent JIA-clinic. The mean age at transfer was 17.8 years for YP transferred to the adult clinic and 15.2 years for transfer to the adolescent clinic. Drop-out of care rate one year after transfer was 5.1% in the adult clinic and 1.3% in the adolescent JIA-clinic. Response rate of the returned questionnaires was 61% for the adolescent JIA clinic and 36% for the adult clinic. There was no difference between responders and non-responders in demographics and disease type besides age (non-responders were significantly younger). Young people transferred to the adult and adolescent JIA-clinic both had high scores on the satisfaction scale (7.7 and 7.5 on the VAS-scale and 72.0 and 74.5 on the OYOF-TES). Self-efficacy scores were high for both groups, with OYOF-SES 59.7 for those transferred to the adult clinic and 58.2 for those transferred to the adolescent JIA-clinic. Conclusion The implementation of the clinical transition pathway has led to a substantial improvement of patient care during the transitional process leading to low drop-out of care rate and high scores on satisfaction with transition. High scores on the self-reported self-efficacy scale suggests confidence of young people to have achieved sufficient skills to successfully manage their disease.